Study on the methods of controlling the fuzzy proportion of the line-following obstacle avoidance of wheeled robots. Issue 3 (2nd April 2020) - Lee, Chun-Hsiung; Liu, Jia-Xiang; Chen, Ke-Chih
Abstract: In the line-following competitions of robots, such as the Asian Competition of Robots Following Black Lines, the robots are expected to follow the designated paths. However, most robots sway when following a straight line at a full speed. Moving forward like this is not so graceful; worse still, robots would derail from the designated lines, making moving inefficient. At present, the full proportion control enables an automatic control system to make different responses to different conditions, a bigger error requires more modification. Of course, the proportion control is not absolutely powerful and cannot control complicated paths, neither can the integral and differential control. It is impossible to make immediate reaction to a right-angled turn. Therefore, this study proposes the methods of controlling the fuzzy proportion of the ling-following obstacle avoidance of wheeled robots, so that robots will be able to achieve line-following obstacle avoidance and quickly reach the destination when taking a complicated path.